Prosperity Teaching in an African Context - Young, Peter R. (African Journal of Theology, 1996)
The "Prosperity Gospel" is one of those aberrations of the Christian gospel born in the West and introduced into Africa by various peripatetic evangelists, including Reinhard Bonnke. Satan is indeed crafty. For the Bible does promise success, blessing and prosperity for those who trust and obey God. But Scripture must interpret Scripture. Theology cannot be based on proof texts isolated from the context.. Peter Young provides a helpful article in which he explores the teachings of the Prosperity Gospel, weighs it in the balance of Scripture and finds it wanting. This article is a clarion call for the church. We need to move away from a shallow and frequently distorted understanding of Scripture to a deeper grasp of biblical truth
free